2020
DOI: 10.2147/rmhp.s273755
|View full text |Cite
|
Sign up to set email alerts
|

<p>Beyond Predicting the Number of Infections: Predicting Who is Likely to Be COVID Negative or Positive</p>

Abstract: Background: This study aims to identify individuals' likelihood of being COVID negative or positive, enabling more targeted infectious disease prevention and control when there is a shortage of COVID-19 testing kits. Methods: We conducted a primary survey of 521 adults on April 1-10, 2020 in Iran, where 3% reported being COVID-19 positive and 15% were unsure whether they were infected. This relatively high positive rate enabled us to conduct the analysis at the 5% significance level. Results: Adults who exerci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It was also evidenced during the COVID-19 pandemic that high PA levels improved sleep quality and mitigated the mental health burden related to a lockdown, such as increased stress, negative emotions, anxiety, depression, or worsening sense of well-being [ 47 , 53 , 54 , 55 , 56 , 59 , 61 , 63 , 65 , 66 , 101 , 102 ]. Physical activity can improve the function of immune and respiratory systems and may predict coronavirus infection [ 104 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also evidenced during the COVID-19 pandemic that high PA levels improved sleep quality and mitigated the mental health burden related to a lockdown, such as increased stress, negative emotions, anxiety, depression, or worsening sense of well-being [ 47 , 53 , 54 , 55 , 56 , 59 , 61 , 63 , 65 , 66 , 101 , 102 ]. Physical activity can improve the function of immune and respiratory systems and may predict coronavirus infection [ 104 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eek et al [ 52 ] showed that people who reported decreased physical activity (PA) levels during the COVID-19 pandemic reported low levels of life satisfaction and aerobic capacity. Moreover, adults who exercise more have a lower risk of being infected with coronavirus [ 53 ]. In the Spanish population, Gonzalez-Bernal et al [ 54 ] recently associated high life satisfaction with fewer days of home confinement, the perception of having received enough information about COVID-19 and its prevention, having private access to the outside, being employed, being male, and not experiencing isolation.…”
Section: Introductionmentioning
confidence: 99%
“…These models have been extended and include additional constructs, such as habits (automatic enactments of a behavior developed through its repeated performance) and perceived risk of infection (personal perceived probability of getting infected). Many studies have shown that these factors were strongly and positively associated with health behaviors adoption in various contexts, including the pandemic [28][29][30][31][32][33].…”
Section: Predictors Of Health Behaviorsmentioning
confidence: 99%